Green Supply Chain and Its Importance in Today's Era Including Covid -Pandemic: Narrative Review Method - Kumar, Kaparthi (International Journal of Supply Chain Management, 2023)
Purpose: The current review investigates how green operations, design, manufacturing, reverse logistics, and waste management are impacted after covid-19 outbreak globally from the available literature. Methodology: A qualitative literature search with integrative models were used by allpying the SEARCH strategy criteria that we used came from a variety of different sources, such as Google scholar, Scopus, World of Science, PubMed, and other online databases. These sources have published the literature on the GSCM during the time of the avian influenza pandemic, as well as the challenges that the supply chain is currently facing and what the learning mantras are. Findings: The present review outlines the existence of the Invariable. Panic resurrects the bullwhip. Some CEOs imagine a corporate whip. Product divisions protect themselves against higher allocations and source's pad. Supply is estimated by suppliers and manufacturers based on customer expectations. Things may be worse. Companies who are prepared with diverse sources and outside-in digital processes will succeed in the new economy. Unique Contribution to Theory, Practice and Policy: By applying the current review gaps the new strategy can be implemented in logistics and supply chain companies for understanding the planning and implementation after post-pandemic.